Fiscal Reconciliation Analysis In The Calculation Of Article 23 Income Tax Obliged To Pt. Dipo International Pahala Otomotif - Rifqy Cheviandri; Yunita Sari Rioni; Junawan Junawan (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This research aims to explain how the reconciliation of income tax article 23 at PT Dipo Internasional Pahala Otomotif. The method used is qualitative descriptive with interview techniques, data classification, comparative analysis and conclusion drawn. This research used company data and archives as a basis for identification to find out whether or not there are differences in fiscal treatment that affect the amount of income tax article 23 payable. The results of this study show how various treatments that apply to fiscal and commercial reports greatly affect the calculation of Income Tax Article 23 and explain that reconciliation is an important part of every transaction activity of a company to monitor it in order to avoid the risk of sanctions. Then the fiscal reconciliation of PT Dipo Internasional Pahala Otomotif is considered to be quite good in accordance with the general provisions of taxation.